2018
DOI: 10.1002/celc.201701231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Pretreatment on the Formation of TiO2 Nanotubes: An Ignored yet Non‐negligible Factor

Abstract: Tailoring the geometric configuration of anodic TiO2 nanotubes enables their use in various applications. This paper demonstrates that the methods for pretreating electrolyte solutions significantly influence the growth of anodic nanotubes. Pretreatment is usually ignored by studies, but is a crucial and non‐negligible factor in the control of nanotube growth. The results indicate that magnetic stirring and ultrasonic agitation facilitate the dissolution and mass transport of ionic species in the solution, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The increase in water content in the electrolyte causes the formation of an initial thick compact oxide layer that also reduces the growth rate of the TiO 2 nanotubes. 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The increase in water content in the electrolyte causes the formation of an initial thick compact oxide layer that also reduces the growth rate of the TiO 2 nanotubes. 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Nickel sulfide (Ni 3 S 2 ), in particular, has been extensively investigated due to its high activity and stability, as well as low cost . Previous works revealed that the structure features, especially surface properties, are crucially important for the electrocatalytic performance of nanocatalysts . Therefore, considerable effort has been devoted to the design and synthesis of unique catalysts with large surface area and readily accessible active sites .…”
Section: Methodsmentioning
confidence: 99%
“…% NH 4 F and 2 vol. % H 2 O . The anodization was performed under alternating applied potential in the form of square wave, i. e., at 40 V for 50 s and then 10 V for 200 s. The total anodization duration was 3 h. The resulting nanotubes were annealed at 450 °C for 3 h in oven (LE140 K1BN, Nabertherm).…”
Section: Methodsmentioning
confidence: 99%